Novel variants and phenotypic heterogeneity in a cohort of 11 Chinese children with Wiedemann-Steiner syndrome - Lin, Yunting; Chen, Xiaohong; Xie, Bobo; Guan, Zhihong; Chen, Xiaodan; Li, Xiuzhen; Yi, Peng; Du, Rong; Mei, Huifen; Liu, Li; Zhang, Wen; Zeng, Chunhua (Frontiers in Genetics, 2023)
Objective: Wiedemann-Steiner syndrome (WSS) is a rare autosomal dominant disorder caused by deleterious heterozygous variants of the KMT2A gene. This study aims to describe the phenotypic and genotypic features of Chinese WSS patients, and assess therapeutic effects of recombinant human growth hormone (rhGH). Methods: Eleven Chinese children with WSS were enrolled in our cohort. Their clinical, imaging, biochemical and molecular findings were analyzed retrospectively. Moreover, the phenotypic features of 41 previously reported Chinese WSS patients were reviewed and included in our analysis. Results: In our cohort, the 11 WSS patients presented with classic clinical manifestations, but with different frequencies. The most common clinical features were short stature (90.9%) and developmental delay (90.9%), followed by intellectual disability (72.7%). The most frequent imaging features were patent ductus arteriosus (57.1%) and patent foramen ovale (42.9%) in cardiovascular system, and abnormal corpus callosum (50.0%) in the brain. In the set comprising 52 Chinese WSS patients, the most common clinical and imaging manifestations were developmental delay (84.6%), intellectual disability (84.6%), short stature (80.8%) and delayed bone age (68.0%), respectively. Eleven different variants, including three known and eight novel variants, of the KMT2A gene were identified in our 11 WSS patients without a hotspot variant. Two patients were treated with rhGH and yielded satisfactory height gains, but one developed acceleration of bone age. Conclusion: Our study adds 11 new patients with WSS, reveals different clinical characteristics in Chinese WSS patients, and extends the mutational spectrum of the KMT2A gene. Our study also shares the therapeutic effects of rhGH in two WSS patients without GH deficiency.